Avaliação clínico-comportamental e histopatológica do encéfalo de gerbils submetidos à isquemia cerebral experimental induzida por oclusão permanente da artéria carótida - Oliveira, Ana Paula Rocha de (2005)
Stroke is caused by the interruption of blood flow in a given vessel, which results in disabling neurological deficits or even death. The high incidence and high cost make stroke reduction a priority and stresses the need for more accurate methods to identify prognoses and appropriate therapeutic forms for rehabilitation in patients. To that end, several experimental studies have been carried out. The use of the Gerbils cerebral ischemia model for the study of clinical, morphological and functional changes occurs due to the fact that the absence of carotid-basilar communication provides this species with an advantage over the others. however, the damaged brain areas have not yet been correlated with these changes. The present study aimed to correlate the clinical and behavioral signs presented with Gerbils' brain morphological changes submitted to experimental ischemia through occlusion of the left carotid artery. Eighteen Gerbils rodents were evaluated, of which 6 were used as controls, 6 false-operated (sham) and 6 underwent permanent cerebral ischemia of the left carotid artery. Clinical manifestations were observed and compared with literature protocols. Changes in motor behavior were verified through the frequency of crossings and surveys, observed in a circular acrylic arena for four days and by analyzing the injury sites in the brain. Behavioral data were subjected to a one-way ANOVA statistical analysis (statistical significance p <0.05). Initially, clinical signs of injury were observed, such as eyelid ptosis, flexion of the forelimb, decreased resistance when pushed and cyclically moved. For motor behavior, there was a statistically significant decrease in the frequencies of crossing (1 °, 3 ° and 4 ° days) and lifting (1 °, 2 °, 3 ° and 4 ° days) in ischemic animals when compared with the group control. The morphological evaluation showed serious injuries, with extensive areas affected by cerebral infarction, such as the hippocampus and cerebral cortex. The areas of infarction were pale, presenting malacia, the presence of macrophages, edema and necrotic changes in neurons and glial cells. As a conclusion, it became evident that motor behavioral changes resulting from ischemia were compatible with the area of ​​injury in the morphological evaluation. This study sought to contribute, through a systematic study of motor correlations and regions susceptible to injury, to a better rehabilitation proposal.